Dissemination of Decision Aids about Hip and Knee Osteoarthritis to Spanish-Speaking Adults through Social Media - K. D. Valentine PhD; Felisha Marques MPH; Antonia F. Chen MD, MBA; Leigh Simmons MD; Karen R. Sepucha PhD (MDM Policy & Practice)
Background Older adults and Hispanic individuals are increasingly turning to social media platforms to access health-related information. The purpose of this project was to evaluate a social media campaign to disseminate information from decision aids (DAs) on hip and knee osteoarthritis to Spanish-speaking adults. Methods A social media marketing team helped create an 8-mo campaign posted across 3 social media platforms to promote visits to a Web site offering free multilingual DAs for treatment of hip or knee osteoarthritis. Eight videos featuring Spanish-speaking actors discussing DAs were boosted (i.e., money was paid so posts landed on user’s feeds). In this observational study, metrics tracked reach, extended engagement, and number of users accessing the Web site. Videos were qualitatively coded for themes, including pain and benefits of treatment options; biserial correlations assessed relationships between the presence of a code and the metrics. We calculated cost per visitor using the total campaign cost and number of users accessing the Web site. Results During the campaign, boosted videos reached 83,937 users. Of the users, 22,777 had extended engagement with the videos, and 1,835 users visited our Web site with access to the DAs. Videos that included themes of pain tended to reach more users ( r  = 0.88) and have higher engagement ( r  = 0.70). When videos included the theme of benefits of treatment, more users tended to visit our Web site ( r  = 0.78). The total campaign cost was $25,950, making the cost per Web site visitor $14.14. Conclusions Social media was a useful, inexpensive tool for disseminating health care information on hip and knee osteoarthritis DAs to predominantly Spanish-speaking adults. Further work should identify how exposure to such social media content affects a viewer’s health care attitudes, health care behaviors, and surgical decision making. Highlights An 8-mo social media campaign was able to reach more than 83,000 users and result in almost 2,000 users accessing a Web site with multilingual decision aids. Social media may be an inexpensive tool for disseminating health care information such as decision aids to Spanish-speaking adults.